Questions about philocryptology - Kornecki, Marek (Folia Philosophica, 2000)
The present article is directly inspired by the author’s reading of Jakub S. Banka’s study „The ontological possibility of verity - "adaequatio". A philocryptological analysis, and it gains its full dialogic sense only in the context of the aforesaid study. The author draws the reader’s attention to two matters connected with the philocryptological analysis; firstly, to the danger of a historicist selection and périodisation of the history of philosophy, and secondly, to the one-sidedness of the metaphysical (or meta-physical) interpretation of the category of being. Pointing to the significant analogies between the idea of philocryptology and the hermeneutic phenomenology, the author emphasises the need for taking into account the results of Husserl's transcendental research, and of Heidegger’s ontological analyses. This seems particularly necessary when we focus, on the one hand, on the connection between the Parmenidcan identity and Kantian transcendental object, and the difference between the ancient Greek unity of sivai and voeiv and the scholastic relation between esse and essentia, on the other. It es exactly the phenomenological experience that shows us that the original truth cannot be described either in an exclusively logical (essentialist), or in an exclusively metaphysical (existential) discourse. The author, while realising the importance of the problems raised by philocryptology, expresses, at the same time, his apprehension lest by uttering the aletheic truth philocryptology should by any chance ,,remove” the philocrypticity of being, which, in consequence, may lead to a repetition of the conclusion of the Hegelian idealist speculation in which the transcendental being seems - from the point of view of a unifying synthesis of thinking of thinking - to be merely an appearance, a „pure nothingness”.